Treatment of appikalny periodontitis with use of the blood plasma enriched with platelets (LLC "Endo Press", 2020)
In structure of stomatologic diseases the periodontitis takes the third place after caries of teeth and a pulpitis, in an age group of 34-47 years the frequency of this form of complications of caries reaches 50%. Results of treatment of a chronic apical periodontitis at 45 patients are given in article. The total of the cured teeth made 47. In the main group (25 patients) applied complex treatment with use of introduction in a periodontium the center of the destruction of tissues behind an apex of osteoplastic materials namely enriched with blood plasma thrombocytes. It is established that use of the specified combination by 30 days promotes acceleration of processes of a reparation of a bone tissue of a periodontium and leads to reduction of terms of treatment. It is confirmed with indicators of optical density of a bone tissue at a chronic apical periodontitis by means of methods of a radioviziografiya and a computer tomography.